Change Of Working Time dan Contribution of Female Worker to Family Income in Gambur Batik Business in Toman Village Babat Toman District - Hartati, Stepenie; Sriati, Sriati (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2023)
Working time allocation is the amount of time allocated to carry out a series of activities that are usually carried out in economic and non-economic activities, the contribution of women workers also plays an important role in family household income. The aims of this study were (1) to describe the processing of Gambir batik (2) to find out the working time of women workers in the economic and non-economic activities of the Gambir batik business (3) to calculate how much the contribution of women workers is to family income. This research was conducted in Toman Village, Tripe Toman District, Musi Banyuasin Regency. The location determination was done purposively. The method used in this research is a survey method. The sampling method was carried out using a non-probability sampling method with a sample of 30 female workers. The data processing method uses descriptive analysis and uses contribution interval scale criteria. The results showed that the Gambir batik processing process consisted of 7 stages consisting of cloth mordant process, pattern making process, cloth pinching process, basic dyeing process, drying process and packaging process. The average time spent working for women workers to earn a living as women workers in the Gambir batik business in Toman Village, Babat Toman District, Musi Banyuasin Regency is 3.54 hours/day or 97.385 hours/month. The contribution of female workers' income to family income is 26.88%, where the range of income contribution is from 20.01-30.00% including moderate contribution